Selected marine mammals of Alaska : species accounts with research and management recommendations - Lentfer, Jack W; United States. Marine Mammal Commission (Washington, D.C. : Marine Mammal Commission, 1988)
". a current summary of the biology and status of ten species of Alaskan marine mammals"--P. iii "PB88-178462"--p. ii Includes bibliographical references Mode of access: Internet.